2021
DOI: 10.1038/s41391-021-00318-3
|View full text |Cite|
|
Sign up to set email alerts
|

Survival outcomes in patients with chemotherapy-naive metastatic castration-resistant prostate cancer treated with enzalutamide or abiraterone acetate

Abstract: Objective Evaluation of the comparative effectiveness of enzalutamide and abiraterone in patients with metastatic castration-resistant prostate cancer (mCRPC) is limited to meta-analyses of randomized trials that exclude patients with significant comorbidities. We evaluated overall survival (OS) in patients with chemotherapy-naive mCRPC treated with enzalutamide or abiraterone acetate (abiraterone) in a real-world single payer setting. Methods A retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 20 publications
5
21
1
Order By: Relevance
“…The median OS rates found in our study are slightly shorter compared to the reported OS rates from the registration studies of enzalutamide and abiraterone acetate (26.8 vs. 35.5 months and 28.4 vs. 34.7 months respectively) [ 35 , 36 ]. Though, our median survival rates are in line with a large previously published real-life cohort of chemotherapy-naïve patients treated with enzalutamide or abiraterone acetate (median OS 29.6 and 25.9 months respectively) [ 37 ]. Our cohort is therefore considered representative for a real-life first line treated cohort of patients with mCRPC.…”
Section: Discussionsupporting
confidence: 86%
“…The median OS rates found in our study are slightly shorter compared to the reported OS rates from the registration studies of enzalutamide and abiraterone acetate (26.8 vs. 35.5 months and 28.4 vs. 34.7 months respectively) [ 35 , 36 ]. Though, our median survival rates are in line with a large previously published real-life cohort of chemotherapy-naïve patients treated with enzalutamide or abiraterone acetate (median OS 29.6 and 25.9 months respectively) [ 37 ]. Our cohort is therefore considered representative for a real-life first line treated cohort of patients with mCRPC.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, a recent systematic review and meta-analysis revealed no significant difference in OS improvement between ENZ and ABI, but ENZ was superior to ABI in improving rPFS and TTPP for patients with metastatic CRPC [25] . In addition, a large retrospective analysis of the Veterans Health Administration database revealed that patients treated with ENZ had a 16% lower risk of death in comparison to those treated with ABI (HR 0.84, 95% CI 0.76–0.94; p = 0.0012) [26] . These data indicate a stronger ability of ENZ to inhibit androgen receptor signaling as a single agent.…”
Section: Discussionmentioning
confidence: 99%
“…It must be noted, however, that abiraterone trials (COU-AA-301, COU-AA-302) used prednisone (an agent with known antitumor activity in mCRPC) as a control arm, whereas enzalutamide trials (AFFIRM, PREVAIL) used placebo as a control arm. Results from a recent retrospective study of 3174 patients with chemotherapy-naive mCRPC treated with first-line enzalutamide or abiraterone acetate, those who received enzalutamide had significantly better OS compared to those who were treated with abiraterone (HR 0.84, 95% CI 0.76-0.94) [45]. The different toxicity profile of abiraterone and enzalutamide may assist during the treatment selection in some men with mCRPC, although they are both generally well tolerated and safe in the vast majority of patients.…”
Section: First-line Mcrpc In Patients Pretreated With Adt Monotherapymentioning
confidence: 99%